TINDAK TUTUR DIREKTIF GURU DALAM KEGIATAN MUHADARAH DI MTsN LUBUK BUAYA KOTA PADANG - Erina Erlis; Novia Juita; Irfani Basri (Bahasa, Sastra, dan Pembelajaran, 2014)
Abstract: The purpose of this research was to describe the forms, strategies and contexs of the teacher’s directive speech acts and the students’ responses toward the teachers’ directive speech acts in delivering learning materials in muhadarah activities at MTsN Lubuk Buaya Kota Padang. The subjects of the research was the teachers delivering materials in muhadarah activities. They were chosen based on the scheduled arranged by school. This was a qualitative researh which used descriptive method. The data collected was the teachers’ directive speech acts in muhadarah activities. The sources of the data were seven teachers delivering materials in that activity. The data gotten was analyzed by inventing, identifying, classifying the forms of directive speech acts, discourse strategy, speech contexts and the students’ responses based on the theory applied. It then was reported and conclusion was drawn. The result of the research indicated  that the directive speech acts forms used in muhadarah activity were requesting, asking question, prohibiting, requiring, permitting, and sugesting. The directive speech acts form that was used frequently was asking questions and that which was rarely used was prohibiting. The strategies of directive speech acts used by the teachers were frankly speaking without courtesy, direct speech with positive politeness, direct speech with negative politeness, and vaguely speaking. The contexts of speech of teachers directive speech acts involved seven teachers as the locutor, and the students as the interlocutor, seven topic, and in average the utterances were produced in quite situation.  The students’ response toward the teacher’s directive speech acts were  responded positively by the students. Kata kunci: tindak tutur direktif, guru,  muhadarah